RNA Interference: A Promising Tool in the Control of Important Vector Born Diseases Zika, Dengue Fever, and Malaria - Jalil Nejati; Mona Koosha; Mohammad Ali Oshaghi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2017)
Background and Objectives: RNA interference is a process, in which a molecule of double-stranded RNA prevents the expression of a particular gene and leads to its silencing. Application of this technology in the control of disease-carrying insects is rising in agriculture and medical sciences. Also, its application in control of insect-borne diseases could be considered as a new, important, and effective approach. In this article, it was attempted to study the mechanisms of RNA interference, routs of its delivery to insects, as well as its application in genetic control of disease vector insects.